FUNCTIONAL CHARACTERISTICS OF DERIVATIONAL AFFIXES IN UZBEK AND ENGLISH: A COMPARATIVE MORPHOLOGICAL ANALYSIS (Journal of Science-Innovative Research in Uzbekistan, 2025)
Derivational affixes play a pivotal role in the expansion and flexibility of vocabulary in natural languages. This study presents a comparative analysis of the functional characteristics of derivational affixes in Uzbek, a Turkic agglutinative language, and English, a Germanic analytic language. Using a descriptive-analytical methodology grounded in morphological theory and corpus linguistics, this article explores how affixation processes differ structurally and semantically. The research emphasizes productivity, semantic transparency, and functional categories involved in derivation. Findings suggest that Uzbek primarily relies on predictable suffixation patterns with high semantic clarity, whereas English exhibits a wider range of affix types with greater variability in meaning and grammatical behavior. These results contribute to typological linguistics and support pedagogical applications in bilingual morphology instruction and computational linguistics.